3D Simulation of Self-Compacting Concrete Flow Based on MRT-LBM. (28th January 2018) - Qiu, Liu-Chao; Han, Yu
Abstract : A three-dimensional multiple-relaxation-time lattice Boltzmann method (MRT-LBM) with a D3Q27 discrete velocity model is applied for simulation of self-compacting concrete (SCC) flows. In the present study, the SCC is assumed as a non-Newtonian fluid, and a modified Herschel–Bulkley model is used as constitutive mode. The mass tracking algorithm was used for modeling the liquid-gas interface. Two numerical examples of the slump test and enhanced L-box test were performed, and the calculated results are compared with available experiments in literatures. The numerical results demonstrate the capability of the proposed MRT-LBM in modeling of self-compacting concrete flows.